Analyzing the Mission and Strategy of Berani Hijrah Community on Developing Islamic Religious Education - Munir, Misbahul; Cahaya, Cahaya; Abdullah, Mulyana; Jenuri, Jenuri; Karim, Abdul Rahim (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The main purpose of this research is to analyze the mission and strategies carried out by Berani Hijrah Community (BHC) on developing Islamic religious education for the younger generation. This research is qualitative with a phenomenological approach. The subject of the study was a community that dared to migrate to Dusun IV, Limau Manis, Tanjung Morawa, Deli Serdang, North Sumatra. Research data in the form of BHC missions and strategies in developing Islamic religious education. Data sources are obtained from all members of the community who dare to migrate. Data collection techniques are carried out by observation, interviews, and documentation. At the same time, data analysis is carried out by data reduction, data presentation, and conclusions. The conclusion of this research is that the courageous migration community employs various strategies, including bringing in popular religious teachers (ustadz) who are liked by teenagers to generate greater enthusiasm in delivering youth-oriented religious lectures. Additionally, the strategies involve increasing parental awareness and involvement, developing a relevant curriculum, establishing study groups and discussions, as well as organizing social and humanitarian activities.